In pursuit of visibility : essays in archaeology, ethnography, and text in honor of Beth Alpert Nakhai - Nakhai, Beth Alpert, 1951-; Ebeling, Jennie R.,; Mazow, Laura B., (Archaeopress Archaeology, 2022)
'In Pursuit of Visibility' honours the distinguished career of a scholar of Canaan and ancient Israel, Beth Alpert Nakhai. In fifteen diverse essays, Professor Nakhai's students and colleagues celebrate her important contributions to the field of Near Eastern Archaeology, including her research into gender, household, and cult in the Bronze and Iron Age southern Levant, and her tireless efforts to acknowledge and support women in the profession. These essays reflect Professor Nakhai's commitment to combining archaeology and text to reconstruct aspects of ancient life and make those who are marginalized visible in both the past and the present.